APLIKASI STOCK OPNAME PRODUK KECANTIKAN KOSÉ BERBASIS ANDROID - Yumnahadi, Sausan Nada; Doharma, Rouli (Infotech: Journal of Technology Information, 2020)
Stock opname is an effort to control the turnover of a product so as not to deviate. The implementation of stock opname is inseparable from the support of the information system, therefore the aim of this study is to analyze the stock opname process of KOSÉ beauty product and to create a suitable application to facilitate the process. Analysis performed using the System Development Life Cycle. Data collection was obtained through interviews, observations, sampling and literature. The application design uses the Object Oriented Programming method. Testing application uses the blackbox method. The results of this study are an android application is made through Kodular and connected to the realtime database of Firebase, but the implementation of the application still has flaws in logic block-coding.